2001
DOI: 10.1128/aem.67.6.2723-2733.2001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacterial Community Composition and Dynamics and Viral Mortality Rates Associated with Enhanced Flagellate Grazing in a Mesoeutrophic Reservoir

Abstract: Bacterioplankton from a meso-eutrophic dam reservoir was size fractionated to reduce (<0.8-m treatment) or enhance (<5-m treatment) protistan grazing and then incubated in situ for 96 h in dialysis bags. Time course samples were taken from the bags and the reservoir to estimate bacterial abundance, mean cell volume, production, protistan grazing, viral abundance, and frequency of visibly infected cells. Shifts in bacterial community composition (BCC) were examined by denaturing gradient gel electrophoresis (DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
324
3
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(355 citation statements)
references
References 54 publications
22
324
3
3
Order By: Relevance
“…However, our study reported the lower abundances of picocyanobacteria than showed by Hennes and Simon (1995). In their study, they have reported in mesotrophic Lake Constance that the abundances of viruses ranged from (10 x4 7 r 10 6 part.mL x1 ), the similar results were also reported by Simek et al (2001) in meso-eutrophic Rimov reservoir (Table 6).…”
Section: Discussionsupporting
confidence: 74%
“…However, our study reported the lower abundances of picocyanobacteria than showed by Hennes and Simon (1995). In their study, they have reported in mesotrophic Lake Constance that the abundances of viruses ranged from (10 x4 7 r 10 6 part.mL x1 ), the similar results were also reported by Simek et al (2001) in meso-eutrophic Rimov reservoir (Table 6).…”
Section: Discussionsupporting
confidence: 74%
“…(ii) The intrinsic low activity of a bacterial group may only allow lysogeny. The Bacteroidetes have been repeatedly found to grow more slowly than other phylogenetic groups (Fuchs et al, 2000;Simek et al, 2001;Zubkov et al, 2001, this study). This metabolic feature may thus represent a signal for the establishment of lysogeny.…”
Section: Changes In Bcc Upon Induction and Ecological Considerationssupporting
confidence: 50%
“…However, in agreement with KtW, the effect of virus-induced mortality was higher in resource-replete treatments, where prokaryotic and viral abundance, prokaryotic and viral production, and virus-induced lysis rates increased (equations 5 and 6). Also, grazing stimulated viral abundance, production, and virus-induced mortality, as found in other studies (72,85,87). Jardillier et al (45) studied the influence of nutrients, grazing, and viral lysis on the prokaryotic community composition in an oligomesotrophic lake and in a eutrophic lake.…”
Section: Combined Effects Of Viral Lysis and Protistan Grazingmentioning
confidence: 64%
“…There are two experimental studies, both conducted in freshwater environments, that manipulated grazing pressure as the sole experimental factor (85,87). Both studies found that prokaryotic and viral activity increased in the presence of grazers and suggest that this stimulation is due to grazer-mediated resource enrichment.…”
Section: Combined Effects Of Viral Lysis and Protistan Grazingmentioning
confidence: 99%